2002
DOI: 10.1111/j.1523-1755.2002.kid573.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of 19-nor-1,25-(OH)2D2 and 1α-hydroxyvitamin D2 on calcium and phosphorus in normal and uremic rats

Abstract: Differential effects of 19-nor-1,25-(OH) 2 D 2 and 1␣-hydroxy-Secondary hyperparathyroidism is a common complicavitamin D 2 on calcium and phosphorus in normal and uremic tion in patients with chronic renal failure. 1,25-(OH) 2 D 3 , rats.the most active metabolite of vitamin D, controls para-Background. Calcitriol, 1,25-(OH) 2 D 3 (1,25D), the most ac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 45 publications
1
18
0
2
Order By: Relevance
“…For example, in CKD clinical studies, paricalcitol's therapeutic index (efficacy vs. hypercalcemic toxicity) is about 3- to 4-fold better than calcitriol, which is reproduced in this kidney disease animal model [37,42]. Consistent with reports by others [37,43], we have previously demonstrated that paricalcitol and doxercalciferol effectively suppress serum PTH at 0.021-0.33 μg/kg in the 5/6 NX rats, but both drugs also induce an increase in serum Ca in the same dose range [39,44]. As a comparison, we show in this report that VS-411, similar to calcitriol, affects serum PTH and Ca in the same dose range, but VS-110 significantly suppresses serum PTH at 0.01-1.0 μg/kg without affecting serum Ca.…”
Section: Discussionsupporting
confidence: 77%
“…For example, in CKD clinical studies, paricalcitol's therapeutic index (efficacy vs. hypercalcemic toxicity) is about 3- to 4-fold better than calcitriol, which is reproduced in this kidney disease animal model [37,42]. Consistent with reports by others [37,43], we have previously demonstrated that paricalcitol and doxercalciferol effectively suppress serum PTH at 0.021-0.33 μg/kg in the 5/6 NX rats, but both drugs also induce an increase in serum Ca in the same dose range [39,44]. As a comparison, we show in this report that VS-411, similar to calcitriol, affects serum PTH and Ca in the same dose range, but VS-110 significantly suppresses serum PTH at 0.01-1.0 μg/kg without affecting serum Ca.…”
Section: Discussionsupporting
confidence: 77%
“…91,92 Despite clinically important PTH suppression, Tan et al found doxercalciferol therapy unacceptably raised serum mineral levels by 13 times in half the ESRD patients in the observational study, totaling 4.9 hypercalcemic episodes and 10.1 hyperphosphatemic episodes per 100 weeks of treatment. 93 In a double-blind RCT investigating doxercalciferol therapy in dialysis patients suffering from moderate-to-severe SHPT, Frazao et al found that 82 of the 99 patients (83%) studied achieved PTH targets but with concomitant mild hypercalcemia and hyperphosphatemia.…”
Section: Doxercalciferolmentioning
confidence: 98%
“…22 In a preclinical murine model, Slatopolsky et al demonstrated that paricalcitol treatment causes reduced intestinal absorption of calcium and phosphorus versus equipotent doses of calcitriol. 109 The cause of this clinical advantage has been investigated on the molecular level and appears to be mediated by transcription of genes in enterocytes. Vitamin D compounds are believed to increase intestinal calcium absorption by up-regulating calcium-transporter-1 (CaT1) on the luminal membrane, calbindin in the cytosol, and plasma membrane calcium ATPase-1 (PMCA1) on the basolateral membrane of enterocytes.…”
Section: Molecular Mechanisms Differentiating Vitamin D-based Therapiesmentioning
confidence: 99%
“…However, nonselective activation of VDR pathways can cause hypercalcemia and hyperphosphatemia by enhanced intestinal absorption of calcium and phosphorus [15] which is associated with increased mortality in dialysis patients [16]. Ideally, management of SHPT in dialysis patients should control PTH levels, while maintaining serum calcium and phosphorus within the normal range, and correct active vitamin D deficiency and inactivation of VDR pathway transcription.…”
Section: Discussionmentioning
confidence: 99%